Long-term diet quality and its change in relation to late-life subjective cognitive decline. Issue 1 (25th September 2021) - Yuan, Changzheng; Cao, Yaying; Ascherio, Alberto; Okereke, Olivia I; Zong, Geng; Grodstein, Francine; Hofman, Albert; Willett, Walter C
ABSTRACT: Background: Evidence regarding the role of diet quality, especially its change, in subjective cognitive decline (SCD) is scarce. Objectives: We aimed to examine associations of long-term diet quality scores, including the Alternate Mediterranean Diet (AMED), Dietary Approaches to Stop Hypertension (DASH), and Alternate Healthy Eating Index 2010 (AHEI-2010), with SCD in the Nurses' Health Study. Methods: We followed 49, 493 female registered nurses (mean age in 1984: 48 y) from 1984 to 2014. Diet scores were derived from 7 repeated FFQs in 1984, 1986, and every 4 y afterward until 2006. Self-reported SCD was assessed in 2012 and 2014 by a 7-item questionnaire on memory and cognition changes. Categorical SCD score was classified as "none" (0 points, 40.8%), "moderate" (0.5–2.5 points, 46.9%), and "severe" (3–7 points, 12.3%). Results: Multinomial and linear regression models were adjusted for total calorie intake, demographic characteristics, lifestyle, and clinical factors. Comparing the top with the bottom quintiles of AMED, DASH, and AHEI-2010, multivariable-adjusted ORs (95% CIs) for severe SCD compared with none were 0.57 (0.51, 0.64), 0.61 (0.55, 0.68), and 0.81 (0.73, 0.90), respectively. Similar associations remained for the 3 diet indexes evaluated 28 y before SCD assessment. Compared with participants with the lowest diet quality tertiles in both remote and recent years, the lowest odds of severe SCD were observed among those who maintained the highest diet quality tertiles over time, with 40%, 32%, and 20% lower odds of severe SCD for AMED, DASH, and AHEI-2010, respectively. Moreover, the odds of severe SCD were lower among those with improved diets over time; for each SD higher in diet quality change, the reductions in risk were 11% for AMED, 5% for DASH, and 3% for AHEI-2010, respectively. Conclusions: Our findings support beneficial roles of long-term adherence to, and improvement in, healthy dietary patterns for the maintenance of subjective cognition in women.